Synergistic Effect of Biopreservation and Vacuum Packaging on the Control of Listeria monocytogenes in Raw Tuna Steaks. - Zarka Amin (KUFOS, 2018)
Abstract- In the present study, Nisin, a bacteriocin produced Lactococcus lactis subsp. lactis, was used as a biopreservative agent against L. monocytogenes in raw Tuna steaks under chilled conditions. In vitro antimicrobial activity and MIC of nisin against L. monocytogenes (ATCC 19111) were determined prior to the application of the 6 different experimental treatments on Yellowfin Tuna (Thunnus albacares) steaks. The treated samples were stored at a chilled temperature (3 ± 0.3 ̊̊ C) for 16 days with the microbiological and biochemical quality assessment done on day 0, 2, 4, 8, 12, 16 and day 0, 4, 8, 12, 16 respectively. While microbiological quality was assessed by determining the total plate count and by enumerating L. monocytogenes, biochemical quality assessment was done by determining TVB-N, TMA-N, pH, PV and FFA for the treated samples.